Metzneria leae Gastón & Huemer, sp. n., a new species from Spain (Lepidoptera: Gelechiidae) - J. Gastón; P. Huemer (SHILAP)
Metzneria leae Gastón & Huemer, sp. n., a new species in the family Gelechiidae, is described from Spain and adults and genitalia of both sexes are figured. The new species differs morphologically and in the DNA barcode from all other known representatives of the genus. Until now, the new species has been confused with Metzneria subflavella Englert, 1974, so both species are compared in detail.